Synthesis Design of Bandpass Filter for UWB Applications with Improved Selectivity - Naghar, Azzeddin; Aghzout, Otman; Alejos, Ana V.; Falcone, Francisco (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper presents the design of UWB threepole modified parallel coupled line bandpass filter with improved rejection in the out-of-band frequencies. To achieve the desired UWB requirements using the conventional bandpass filter design, a physical dimension optimization of space-gap between lines, line widths and lengths was applied. An equivalent circuit model is also presented and demonstrates reasonable agreement with simulation results. The optimized filter demonstrates an excellent UWB performance, covering the Federal Communication Commission spectrum bandwidth with low insertion loss and acceptable selectivity. However, this resulting filter structure presents very small gapping between adjacent resonators; that means the filter is unmanufactured. Then an example of an alternative filter structure is finally proposed with null gaping and shortcircuited stubs that yields to a fabricated prototype with selectivity improvement. Generally speaking, reasonable agreement is achieved between measurement and simulation results.